Effects of membrane adhesion barriers on wound healing reaction after glaucoma filtration surgery: A comparative study with Interceed and Seprafilm - Akyol, N; Aydogan, S; Akpolat, N (Wichtig Editore, 2005)
PURPOSE. To evaluate and compare the effectiveness of two adhesion barriers, Interceed and Seprafilm, on wound healing reaction after glaucoma filtration surgery. MATERIALS AND METHODS. Full-thickness filtration surgery was carried out on three groups, each containing four rabbits. Interceed and Seprafilm prepared in 3x4 mm dimensions was put on and around scleral opening in Groups 1 and 2, respectively. All groups received tobramycin and dexamethasone drops tid for 14 days. Intraocular pressure (IOP), anterior chamber depth, and bleb appearance were checked on the first, third, seventh, and 14th days. The rabbits were killed on the 14th day and the trabeculectomy area with overlying conjunctiva was excised. The samples were fixed with 10% formalin, buried in paraffin, and stained with hematoxylin and eosin. The surgical site and surrounding subconjunctival area were evaluated histopathologically for cell counts (fibroblast, lymphocyte, eosinophil, and macrophage), presence of edema and foreign body reaction, and potency of the fistula tract. RESULTS. Mean IOP at the first and third day examinations was significantly different between groups, but there was no statistically significant difference among the groups with respect to IOP, anterior chamber depth, or bleb appearance at the seventh and 14th days. The groups were similar with respect to number of fibroblasts, eosinophils, and neutrophils. Number of macrophages was significantly increased in Groups 1 and 2 and number of vessels was significantly decreased in Group 1. CONCLUSIONS. Neither of these two adhesion-preventing substances seems to suppress wound healing reaction after glaucoma filtration surgery. However, a diminished wound healing reaction was expected with a decreased number of vessels, such as in Group 1. Increased number of macrophages in both groups may result in a decreased level of some inflammatory mediators.
Keywords: interceed; Seprafilm; filtration surgery; wound healing